Preparation method of flexible aerogel with porous bionic noise reduction structure

Flexible aerogel is prepared by composited carbon nanotubes and polymer sponges to form a nanopore structure, which solves the problem of unstable sound absorption and noise reduction performance of materials in the prior art, and achieves efficient noise reduction effect and simplification of the process.

CN119591932BActive Publication Date: 2025-04-22THE SIXTH MEDICAL CENT OF THE CHINESE PEOPLES LIBERATION ARMY GENERAL HOSPITAL +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510139779.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-22
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

In the prior art, harmful substances and complex dispersion preparation methods are required to prepare aerogel materials, resulting in unstable sound absorption and noise reduction performance of the material.

Method used

Flexible aerogels are made by composite carbon nanotubes and polymer sponges, and a transparent and flexible nanopore structure is formed through technologies such as ultrasonic dispersion, vacuum filtration and high-pressure air pressure.

Benefits of technology

It realizes efficient noise reduction performance, especially better suppression function for low-frequency noise, and simplifies the preparation process and avoids the use of harmful substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591932B_ABST
    Figure CN119591932B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of preparation of noise reduction and sound absorption materials, and specifically relates to a method for preparing a flexible aerogel with a porous bionic noise reduction structure. The preparation method comprises: placing a high-concentration carbon nanotube dispersion and a fully open-pore sponge under vacuum conditions, so that the carbon nanotube dispersion is absorbed into the fully open-pore sponge; taking out the sponge that fully and evenly absorbs the carbon nanotube dispersion, drying and curing to obtain a flexible aerogel with a porous bionic noise reduction structure. The preparation method uses carbon nanotubes and polymer sponges to composite and manufacture a transparent and flexible nanoporous structure, thereby imitating the protective structure of the human auditory system, and has good noise reduction performance, especially better suppression function for low-frequency noise.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of noise reduction and sound absorption materials, and in particular relates to a method for preparing a flexible aerogel with a porous bionic noise reduction structure. Background Art

[0002] At present, the main method of noise reduction is to absorb and isolate noise by using sound-absorbing and sound-insulating materials, which is called passive noise reduction. Another method is active noise reduction, which extracts the noise spectrum in the external field and uses the anti-phase wave to cancel the noise. In addition to the active noise reduction method of canceling by emitting anti-phase waves, there is also an active noise reduction method that uses damping materials to suppress structural vibration and reduce noise.

[0003] Bionic research on the human auditory system has found that the human cochlea is protected by a transparent and flexible porous structure, which can effectively reduce and filter noise that is harmful to human hearing. Figure 1 As shown, it can reduce the energy of sound entering the auditory system through tiny nanopore channels. At the same time, the nanostructure vibrates regularly with sound waves, which can better absorb and eliminate noise of certain frequencies, such as low-frequency noise.

[0004] Chinese patent application CN116986888A discloses a low-cost method for preparing fiber-reinforced aerogels. The aerogels prepared by this method have good toughness and mechanical strength, can be extruded, and will not break or deform after extrusion; they also have extremely high corrosion resistance, heat insulation, sound insulation and unique air permeability. However, this method requires the use of harmful substances such as concentrated sulfuric acid, potassium permanganate and hydrochloric acid, and its dispersion preparation method is complicated, and its practical application is cumbersome; the nanopowder is unevenly distributed inside the porous material, and the sound absorption and noise reduction performance is unstable.

[0005] Therefore, there is an urgent need to develop a method for preparing a flexible aerogel with a porous bionic noise reduction structure that has a simple process and improves the sound absorption and noise reduction performance of the aerogel. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a flexible aerogel with a porous bionic noise reduction structure. The method uses carbon nanotubes and polymer sponges to composite and manufacture a transparent and flexible nanoporous structure, thereby imitating the protective structure of the human auditory system, having good noise reduction performance, especially having better suppression function for low-frequency noise.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a flexible aerogel having a porous bionic noise reduction structure, the preparation method comprising:

[0009] 1) adding carbon nanotubes to the solution, and stirring and dispersing by ultrasonication to obtain a 0.15-0.3 mol / L carbon nanotube dispersion; vacuum filtering the carbon nanotube dispersion, and after filtering out part of the solution, increasing the concentration of the carbon nanotube dispersion to 0.5-1 mol / L;

[0010] 2) Put the high-concentration carbon nanotube dispersion and the fully open-pore sponge into a vacuum box, evacuate the vacuum box until small bubbles appear in the carbon nanotube dispersion, and stop evacuating; then use a press to compact the fully open-pore sponge under vacuum conditions, so that the pores inside the fully open-pore sponge are completely flattened and the air inside the sponge is discharged; then slowly release the pressure, and when the fully open-pore sponge rebounds, the carbon nanotube dispersion is absorbed into the fully open-pore sponge;

[0011] 3) After the fully open-pore sponge has fully rebounded, high-pressure air at a pressure of 3-5 atmospheres is introduced into the vacuum box to completely press the carbon nanotube dispersion into the sponge; ultrasonic vibration is performed for 2-3 hours to keep the carbon nanotube content inside and outside the fully open-pore sponge consistent;

[0012] 4) Take out the sponge that has fully and evenly absorbed the carbon nanotube dispersion, put it into a drying oven, and dry it at 50-80°C for 10-48 hours;

[0013] 5) The dried sponge is cured to obtain a flexible aerogel with a porous bionic noise reduction structure, the curing temperature is 250-300° C., and the curing time is 0.5-30 minutes.

[0014] Preferably, the carbon nanotubes are industrial-grade carbon nanotubes with a diameter of 6-12 nanometers and a length of 5-20 micrometers.

[0015] Preferably, the solution is water and / or ethanol.

[0016] Preferably, the ultrasonic dispersion stirring is stirring while ultrasonicating, the ultrasonic temperature is 30-50° C., and the ultrasonic time is 30 minutes to 60 minutes.

[0017] Preferably, the fully open-cell sponge is obtained by treating a closed-cell sponge with cold pressing and blasting, and the pressure of the cold pressing and blasting is 0.5-10 MPa / m 2 .

[0018] Preferably, the closed-cell sponge is selected from polyurethane sponge, melamine sponge and polyester sponge.

[0019] Preferably, the content of carbon nanotubes in the flexible aerogel with a porous bionic noise reduction structure is 0.5-1 mol / L, the diameter of the carbon nanotubes is 6-12 nanometers, and the length is 5-20 micrometers.

[0020] The vacuum filtration of the present invention is to extract a high-concentration carbon nanotube dispersion liquid by using a vacuum filtration device. An industrialized micron quantitative filter paper or an industrialized semipermeable membrane is placed on the funnel, and a vacuum is drawn under the funnel, which can accelerate the filtration of excess water and ethanol to obtain a high-concentration carbon nanotube dispersion slurry.

[0021] The porous support skeleton used in the present invention is made of closed-cell polymer sponge (such as polyurethane sponge, polyester sponge and melamine sponge, etc.), which is subjected to cold pressing and explosion treatment (pressure of 0.5-10MPa / m 2 ). The isolation film between the pores inside the closed-cell sponge is crushed by pressure to form open pores. The crushed film will form fine fibers attached to the supporting skeleton inside the sponge. Compared with ordinary open-cell sponges, the pressure explosion method greatly increases the fiber content inside the sponge. While forming open pores to enhance permeability, it helps to contain more carbon nanotubes and fix the carbon nanotubes through the internal fibers, so that the nanoporous structure formed by the carbon nanotubes will not scatter from the sponge pores.

[0022] The present invention uses vacuum extrusion to uniformly extrude high-concentration carbon nanotube dispersion into the interior of the polymer sponge.

[0023] The present invention is to completely fill the high-concentration carbon nanotubes into the sponge, and after the sponge fully rebounds, the dispersion liquid needs to be completely pressed into the sponge by high-pressure air. The high-pressure air can be provided by compressed air, and the pressure is 3-5 atmospheres.

[0024] In the present invention, since the sponge has a certain filtering effect on carbon nanotubes, the carbon nanotube content inside the sponge will be less than that on the surface, so ultrasonic vibration is required to keep the carbon nanotube content inside and outside the sponge consistent.

[0025] The method for preparing the carbon nanotube dispersion liquid of the present invention is simple, and can be directly dispersed by using a solution without using an oxidant to oxidize the carbon nanotubes. The dispersion effect is good and no agglomeration occurs.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The binder will cause the formed pores to be blocked, and a completely transparent nanoporous structure cannot be formed. The present invention uses carbon nanotubes to form a stable nanoporous structure in a polymer sponge without adding any binder; the nanoporous structure is completely transparent and flexible; the nanoporous structure simulates the noise reduction working principle of human hearing and can vibrate with sound waves to offset the energy of sound waves;

[0028] 2. The content of carbon nanotubes in the porous bionic noise reduction structure carbon nanotube aerogel of the present invention is 0.5-1 mol / L, the diameter of the carbon nanotubes is 6-12 nanometers, and the length is 5-20 micrometers, and the noise reduction effect is the best;

[0029] 3. The nano-bionic noise reduction aerogel of the present invention has extremely strong absorption performance for sound, especially the absorption performance of low-frequency sound waves is much higher than that of other materials; it has good processing performance and can be made into various shapes and specifications. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A diagram of a flexible porous protective structure for wrapping the human cochlea;

[0031] Figure 2 This is an electron microscope image of a flexible aerogel composed of carbon nanotubes. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0033] A method for preparing a flexible aerogel having a porous bionic noise reduction structure, the preparation method comprising:

[0034] 1. Preparation of high concentration carbon nanotube powder dispersion:

[0035] 1) Mix the carbon nanotubes into the solution at a ratio of 0.15-0.3 mol / L, and stir evenly with a stirring rod; the solution can be pure water or ethanol or a mixture of pure water and ethanol. When a mixture of water and ethanol is used, the volume concentration of ethanol is 0-98%.

[0036] 2) After the carbon nanotube powder is evenly dispersed in the solution, turn on the ultrasound and heat the mixed solution to 30-50°C for ultrasonic dispersion;

[0037] 3) During ultrasonic dispersion, continue to use a stirring rod to stir the mixture and observe whether there are carbon nanotube powder particles adhering to the stirring rod;

[0038] 4) After 30-60 minutes of ultrasonic dispersion, observe that there are no carbon nanotube powder particles adhering to the stirring rod, and there are no agglomerated carbon nanotube powders around and at the bottom of the container, and turn off the ultrasonic and heating functions;

[0039] 5) Place the mixed solution in a vacuum filtration device and filter using micron quantitative filter paper or a semipermeable membrane;

[0040] 6) During filtration, the mixed solution is not stirred. After filtering out part of the solution, the concentration of nanopowder in the dispersion can be increased from 0.15-0.3mol / L to 0.5-1mol / L (500-1000mol / m3 ), and through the previous ultrasonic dispersion, the carbon nanotube powder and the solution are completely mixed, which not only increases the concentration, but also prevents agglomeration, making it suitable for large-scale production.

[0041] In the dispersion preparation step, in order to solve the problem of high carbon nanotube powder content, easy agglomeration and uneven dispersion when preparing carbon nanotube dispersion in batches, the present invention first prepares a low-concentration carbon nanotube dispersion, and then filters out part of the solution through vacuum filtration technology, thereby increasing the concentration of carbon nanotubes in the dispersion. Through this technology, the high-concentration dispersion has a high carbon nanotube content, is evenly dispersed, does not agglomerate, and can better enter and be evenly dispersed in the polymer sponge.

[0042] 2. Prepare a polymer sponge with a three-dimensional network support structure:

[0043] 1) When using high molecular foaming materials such as polyurethane sponge, melamine sponge, and polyester sponge, these materials need to be opened first to prevent the appearance of closed pores, which will affect the penetration of nanopowder dispersion in them;

[0044] 2) Cold pressing and explosion method can be used, and the polymer foam material is placed on a pressure device (conventional mechanical equipment in this field) for extrusion. After extrusion, the closed cells inside can be fully opened to form a fully open-pore structure (the meaning of fully open-pore is that the diaphragms between all the pores inside the sponge are opened), which has a stronger absorption capacity for nanopowder dispersion. Compared with other sponge opening methods, the advantage of the explosion method is that the sponge after explosion has more fiber structures in the sponge body, these fiber structures can contain more carbon nanotubes and enhance the flexibility of the nanostructure.

[0045] Generally speaking, a transparent nanoporous structure can be obtained by drying a nanopowder dispersion, but the carbon nanotube powder is only sintered at high temperature without external assistance, and its sintered strength is very low, easy to crack, and will break at the touch. Therefore, it is necessary to use other three-dimensional network support structures to fix it, such as polyurethane sponge, melamine sponge, polyester sponge, etc.

[0046] 3. In a vacuum box, use pressure to infiltrate the carbon nanotube powder dispersion into the polymer sponge with a three-dimensional network structure:

[0047] 1) Soaking the fully open-pore sponge obtained by compression in a carbon nanotube dispersion and placing it in a vacuum box with a pressure device;

[0048] 2) To prevent the boiling of water due to too low air pressure, the vacuum degree of the vacuum box shall not be lower than 0.08MPa;

[0049] 3) The pressure equipment in the vacuum box squeezes the polymer sponge soaked in the dispersion to help remove the air inside the sponge and absorb the carbon nanotubes in the dispersion into the polymer sponge. Use a press to compact the sponge under vacuum conditions, completely flatten the pores inside the sponge, and expel the air inside the sponge. Then slowly release the pressure, and when the sponge rebounds, the carbon nanotube dispersion will be absorbed into the sponge.

[0050] In order to completely fill the high-concentration carbon nanotubes into the sponge, the dispersion needs to be completely pressed into the sponge by high pressure after the sponge fully rebounds. The high pressure can be provided by introducing compressed air, with a pressure of 3-5 atmospheres.

[0051] The vacuum box used in this step can be a vacuum sealed barrel, and the vacuum sealed barrel adopts a vacuum sealed barrel for conventional experiments in the field, and the pressure head of the press is placed in the sealed barrel. The hydraulic pipe of the press passes through the lid of the vacuum sealed barrel to connect the pressure pump, and the hydraulic pipe and the lid of the vacuum sealed barrel are sealed with silicone. Here, the full-open-pore sponge is squeezed under a vacuum environment to ensure that the air inside the sponge is completely excluded, so that the dispersion liquid penetrates into the inside of the sponge, and the carbon nanotubes are evenly distributed inside the sponge. When high-pressure air is introduced, the vacuum sealed barrel is equivalent to a sealed container. At this time, the pressure in the barrel increases, and the dispersion liquid is further pressed into the full-open-pore sponge.

[0052] Since the sponge has a certain filtering effect on carbon nanotubes, the carbon nanotube content inside the sponge will be less than that on the surface. Therefore, ultrasonic vibration is required to keep the carbon nanotube content inside and outside the sponge constant. The ultrasonic time is 2-3 hours.

[0053] The common soaking method of infiltrating the carbon nanotube dispersion into the polymer sponge easily causes the carbon nanotube powder to gather around the polymer sponge, but it is difficult to enter the inside of the polymer sponge. Under a vacuum environment, the pressure extrusion method can more effectively remove the air inside the polymer sponge, increase the flow of the carbon nanotube dispersion inside the polymer sponge, and make the polymer sponge absorb the carbon nanotubes more fully.

[0054] The present invention uses a prepared high-concentration dispersion to extrude into the sponge at one time, which is beneficial to control the content of carbon nanotubes in the sponge and better control the internal nanopore structure. Earlier patents used a method of multiple immersions. Although each immersion can increase a certain amount of nanopowder content, the nanopowder that was previously infiltrated into the sponge will fall off during the immersion steps such as immersion, vibration and extrusion, resulting in the increase in the amount of nanopowder each immersion is difficult to control and a large error. In addition, the nanopowder inside the sponge falls off during the immersion step, which will block the pores and affect the penetration of the nanopowder into the sponge, resulting in high external content, low internal content, unevenness, large manufacturing randomness, and large errors in structure and performance parameters. Therefore, a one-time immersion can solve the above problems, greatly improve the stability, uniformity, and consistency of the material, and at the same time improve the performance indicators of the material.

[0055] 4. Drying:

[0056] The polymer sponge that has fully absorbed the carbon nanotube dispersion is taken out and placed in a drying box. The material is dried by heating at a temperature of 50-80° C. The drying time is 10-48 hours.

[0057] 5. Thermosetting:

[0058] The dried carbon nanotubes in the polymer sponge are only connected together by mechanical structures. This connection structure is very fragile and will fall apart when encountering external forces. At this time, the dried sample needs to be heated to make the polymer material in the sponge in a semi-melted state, so that the carbon nanotubes can be firmly bonded to the polymer skeleton in the sponge without using any adhesive. The solidified sample can have very high mechanical stability. The preferred heating temperature is 250-300°C. When using an ordinary muffle furnace, the heating time is 10-30 minutes; when using a microwave drying furnace, the heating time is 0.5-2 minutes.

[0059] Embodiment 1:

[0060] Take 0.75 mol of carbon nanotube powder and pour it into 5 liters of pure water. Stir it evenly with a stirring rod, turn on ultrasound, heat the mixture to 50°C, and perform ultrasonic dispersion. After 1 hour of ultrasound, observe that there are no carbon nanotube powder particles adhering to the stirring rod, and there is no agglomerated carbon nanotube powder around and at the bottom of the container. Turn off the ultrasound and heating functions. Put the mixed solution into a vacuum filtration device and filter it using an industrial semipermeable membrane (such as Toray TM720D-400, pore size 0.01μm). During filtration, the mixed solution is not stirred. After filtering out part of the solution, the concentration of carbon nanotube powder in the dispersion is increased to 0.7mol / L.

[0061] A polyurethane sponge (15cm×15cm×6cm) was subjected to compression and explosion treatment, soaked in a carbon nanotube dispersion, and placed in a vacuum box (vacuum degree 0.08MPa). The polyurethane sponge was squeezed to help remove the air inside. After the polyurethane sponge fully rebounded, 3 atmospheres of high-pressure air was introduced to allow the dispersion to fully enter the sponge. Ultrasonic vibration was then performed for 3 hours to evenly disperse the carbon nanotube powder inside the sponge.

[0062] The polyurethane sponge that fully and evenly absorbed the carbon nanotube dispersion was taken out and placed in a drying oven. The material was dried at a heating temperature of 80°C for 30 hours. The temperature was then raised to 300°C and the heating treatment was continued for 30 minutes. The carbon nanotubes in the prepared aerogel material were evenly distributed, and no powder fell off after pressing. The sound absorption coefficient was measured by the impedance tube sound absorption coefficient test method, see Table 1.

[0063] Embodiment 2:

[0064] Take 0.50mol of carbon nanotube powder and pour it into 4 liters of 50% ethanol aqueous solution by volume, stir it evenly with a stirring rod, turn on ultrasound, heat the mixture to 40°C, and perform ultrasonic dispersion. After 40 minutes of ultrasound, observe that there are no carbon nanotube powder particles adhering to the stirring rod, and there is no agglomerated carbon nanotube powder around and at the bottom of the container. Turn off the ultrasound and heating functions. Put the mixed solution into a vacuum filtration device and filter it using an industrial semipermeable membrane. During filtration, the mixed solution is not stirred. After filtering out part of the solution, the concentration of carbon nanotube powder in the dispersion increases to 0.8mol / L.

[0065] A polyester sponge (15cm×15cm×6cm) was subjected to compression and explosion treatment, soaked in a carbon nanotube dispersion, and placed in a vacuum box (vacuum degree 0.08MPa). The polyester sponge was squeezed to help remove the air inside. After the polyester sponge fully rebounded, 3 atmospheres of high-pressure air was introduced to allow the dispersion to fully enter the sponge. Ultrasonic vibration was then performed for 3 hours to evenly disperse the carbon nanotube powder inside the sponge.

[0066] The polyester sponge that has fully and evenly absorbed the carbon nanotube dispersion is taken out and placed in a drying oven. The material is dried at a heating temperature of 70°C for 20 hours. The temperature is then raised to 270°C and the heating treatment is continued for 20 minutes. The carbon nanotubes in the prepared aerogel material are evenly distributed, and no powder falls off after pressing. The sound absorption coefficient is measured by the impedance tube sound absorption coefficient test method, see Table 1.

[0067] Embodiment 3:

[0068] Take 1.0mol of carbon nanotube powder and pour it into 5 liters of 60% ethanol aqueous solution by volume, stir it evenly with a stirring rod, turn on ultrasound, heat the mixture to 45°C, and perform ultrasonic dispersion. After 50 minutes of ultrasound, observe that there are no carbon nanotube powder particles adhering to the stirring rod, and there is no agglomerated carbon nanotube powder around and at the bottom of the container. Turn off the ultrasound and heating functions. Put the mixed solution into a vacuum filtration device and filter it using an industrial semipermeable membrane. During filtration, the mixed solution is not stirred. After filtering out part of the solution, the concentration of carbon nanotube powder in the dispersion increases to 0.6mol / L.

[0069] A polyurethane sponge (15cm×15cm×6cm) was subjected to compression and explosion treatment, soaked in a carbon nanotube dispersion, and placed in a vacuum box (vacuum degree 0.08MPa). The polyurethane sponge was squeezed to help remove the air inside. After the polyurethane sponge fully rebounded, 4 atmospheres of high-pressure air was introduced to allow the dispersion to fully enter the sponge. Ultrasonic vibration was then performed for 2 hours to evenly disperse the carbon nanotube powder inside the sponge.

[0070] The polyurethane sponge that has fully and evenly absorbed the carbon nanotube dispersion is taken out and placed in a drying oven. The material is dried at a heating temperature of 60°C for 48 hours. The temperature is then raised to 300°C and the heating treatment is continued for 30 minutes. The carbon nanotubes in the prepared aerogel material are evenly distributed, and no powder falls off after pressing. The sound absorption coefficient is measured by the impedance tube sound absorption coefficient test method, see Table 1.

[0071] Embodiment 4:

[0072] Take 1.2 mol of carbon nanotube powder and pour it into 4 liters of 98% ethanol. Stir it evenly with a stirring rod, turn on ultrasound, heat the mixture to 30°C, and perform ultrasonic dispersion. After 30 minutes of ultrasound, observe that there are no carbon nanotube powder particles adhering to the stirring rod, and there is no agglomerated carbon nanotube powder around and at the bottom of the container. Turn off the ultrasound and heating functions. Put the mixed solution into a vacuum filtration device and filter it using micron quantitative filter paper. During filtration, the mixed solution is not stirred. After filtering out part of the solution, the concentration of nanopowder in the dispersion increases to 1 mol / L.

[0073] The melamine sponge (15cm×15cm×6cm) was subjected to compression and explosion treatment, soaked in the carbon nanotube dispersion, and placed in a vacuum box (vacuum degree 0.08MPa), and the melamine sponge was squeezed to help remove the air inside. After the melamine sponge fully rebounded, 5 atmospheres of high-pressure air was introduced to allow the dispersion to fully enter the sponge. Ultrasonic vibration was then performed for 2 hours to evenly disperse the carbon nanotube powder inside the sponge.

[0074] The melamine sponge that fully absorbed the carbon nanotube dispersion was taken out and placed in a drying oven. The material was dried at a heating temperature of 50°C for 10 hours. The dried material was then placed in a microwave drying oven, the temperature was controlled to 250°C, and the heating time was 2 minutes. The electron microscope image of the prepared aerogel material is shown below: Figure 2 As shown, from Figure 2 It can be seen that the aerogel material has a porous bionic noise reduction structure similar to the flexible porous structure of the human cochlea, with a pore size of about 5-30 microns. The carbon nanotubes in the prepared aerogel material are evenly distributed and have very good sound absorption performance. The sound absorption coefficient measured by the impedance tube sound absorption coefficient test method is shown in Table 1.

[0075] Table 1 Comparison of sound absorption coefficients of porous bionic noise reduction structure aerogel of the present invention and other materials

[0076]

[0077] It can be seen from Table 1 that the overall sound absorption coefficient of the fiber reinforced aerogel prepared by the method of the present invention is higher than that of other sound insulation materials, especially in the low-frequency stage, the sound absorption coefficient is close to 1, reaching more than 0.98.

[0078] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.

[0079] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a flexible aerogel having a porous bionic noise reduction structure, the preparation method comprising: 1) Add carbon nanotubes to the solution, disperse and stir by ultrasonication to obtain a 0.15-0.3 mol / L carbon nanotube dispersion; The carbon nanotube dispersion is subjected to vacuum filtration, and after filtering out a portion of the solution, the concentration of the carbon nanotube dispersion is increased to 0.5-1 mol / L; 2) Put 0.5-1mol / L carbon nanotube dispersion and fully open-pore sponge into a vacuum box, evacuate the vacuum box until small bubbles appear in the carbon nanotube dispersion, and stop evacuating; then use a press to compact the fully open-pore sponge under vacuum conditions, so that the pores inside the fully open-pore sponge are completely flattened and the air inside the sponge is discharged; then slowly release the pressure, and when the fully open-pore sponge rebounds, the carbon nanotube dispersion is absorbed into the fully open-pore sponge; 3) After the fully open-pore sponge has fully rebounded, high-pressure air at a pressure of 3-5 atmospheres is introduced into the vacuum box to completely press the carbon nanotube dispersion into the sponge; ultrasonic vibration is performed for 2-3 hours to keep the carbon nanotube content inside and outside the fully open-pore sponge consistent; 4) Take out the sponge that has fully and evenly absorbed the carbon nanotube dispersion, put it into a drying oven, and dry it at 50-80°C for 10-48 hours; 5) The dried sponge is subjected to microwave curing to obtain a flexible aerogel with a porous bionic noise reduction structure, the curing temperature is 250-300°C, and the curing time is 0.5-2 minutes; The fully open-cell sponge is obtained by treating a closed-cell sponge with cold pressing and explosion, wherein the pressure of the cold pressing and explosion is 0.5-10 MPa; and the closed-cell sponge is a melamine sponge.

2. The preparation method according to claim 1, characterized in that: The carbon nanotubes have a diameter of 6-12 nanometers and a length of 5-20 micrometers.

3. The preparation method according to claim 1, characterized in that: The solution is water and / or ethanol.

4. The preparation method according to claim 1, characterized in that: The ultrasonic dispersion stirring is stirring while ultrasonicating, the ultrasonic temperature is 30-50° C., and the ultrasonic time is 30 minutes to 60 minutes.

Citation Information

Patent Citations

  • Preparation method of low-cost fiber reinforced aerogel

    CN116986888A

  • Method for preparing carbon nanotube modified hydrophobic and oleophylic melamine sponge through solution impregnation process

    CN107876033A

  • Macromolecule sponge sound absorption composite material and preparation method thereof

    CN109749402A